Fixed or open-ended? Labor contracts and productivity in the Colombian manufacturing sector - Francesca Castellani; Giulia Lotti; Nathalie Obando (Inter-American Development Bank (IDB), 2017)
Using the Colombian Annual Manufacturing Survey (AMS) between 2000 and 2014, this paper investigates the effect of labor contract modalities on firm productivity within the industrial sector through a structural model. We find that temporary workers contribute to firms' labor productivity to a lower extent than permanent workers, while also having detrimental effects on TFP dynamics. We show this result is unlikely to be driven by the different skill composition of workers holding temporary contracts.
Keywords: C14; C52; D24; J23; J24; J41; 330; labor contracts; temporary workers; skilled workers; firms' TFP